LATIHAN LOMPAT TALI SATU TUNGKAI BERGANTIAN DAN SATU TUNGKAI BERTURUT-TURUT DAPAT MENINGKATKAN POWER OTOT TUNGKAI ATLET TARUNG DERAJAT PRINGGABAYA TAHUN 2020 - Selviana, Rina; Jamaludin, Jamaludin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research is based on the lack of form of training to increase leg muscle power so that it affects the leg power ability of athletes during a fight or championship, whereas having good power will be a reliable attack, especially leg muscle power for kicks. For this reason, researchers aim to increase leg muscle power by alternating one leg jumping rope and one leg jumping rope training respectively. The method used to conduct this research was the experimental method with a two-grob pre-test post-test design. In this study, the samples of this study were all athletes who took part in the training in the middle pringga-middle level training, totaling 20 people. Instrumren used in this research is to use vartical jumdan to collect evidence related to data supporting the research results is using the documentation method. The data analysis used to process the data obtained in the field was using the t-test formula. The results of this study were that after the analysis was carried out with the t-test formula, the t-value value was greater than the t-table value for a group of athletes who were given one leg jump rope training treatment, so it can be concluded that there is an effect of jumping rope training. One leg alternates with the Leg Muscle Power of Pringgabaya-degree Tarung Athletes in 2020. Whereas for the group that was given one leg jump rope training in a row the t-count value was greater than the t-table value so that in this group it could also be concluded that there was an influence One leg rope training in a row against the leg muscle power of Pringgabaya athletes in 2020